Hourly differences in air pollution on the risk of asthma exacerbation. (August 2015) - Kim, Jayeun; Kim, Ho; Kweon, Jung
Abstract: We investigated the association between hourly differences in air pollution and asthma exacerbation in Korea using asthma-related emergency department data and verified seasonality and demographic modifiers with an hourly temporal resolution. We applied time-stratified case-crossover adjusted for weather and influenza; the lag was stratified as 1–6, 7–12, 13–18, 19–24, 25–48, and49–72 h. Odds ratios (95% confidence interval) per interquartile range increase were 1.05 (1.00–1.11) after 1–6 h for PM10–2.5 and 1.10 (1.04–1.16) after 19–24 h for O3 . Effect size was 1.14 (1.06–1.22) at a 1–6 h lag in spring for PM10–2.5, and 1.25 (1.03–1.51) at a 25–48 h lag in winter for O3 . O3 effects were age- and low socio-economic status-modified at a 7–12 h lag [1.25 (1.04–1.51)]. Increased PM10–2.5 and O3 increased the risk of asthma exacerbation; the effect of PM10–2.5 was most immediate. Highlights: We examined hourly differences in air pollution levels and asthma exacerbation risk. Increased PM10–2.5 and O3 levels increased the risk of asthma exacerbation. The effect of PM10–2.5 was more immediate than other pollutants. The effect of O3 was modified by age and socio-economic status. O3 has a longer lag effect, particularly in winter. Abstract : Hourly increments of PM10–2.5 and O3 induced an increased risk of asthma-related emergency room visits, and the effect of PM10–2.5 was most immediate.